2021
DOI: 10.3389/frwa.2021.728730
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Adaptive Capacity to Flooding in Urban Environments: Social Capital, Social Vulnerability, and Risk Perception

Abstract: To effectively cope with the impacts of climate change and increase urban resilience, households and neighborhoods must adapt in ways that reduce vulnerability to climate-related natural hazards. Communities in the United States and elsewhere are exposed to more frequent extreme heat, wildfires, cyclones, extreme precipitation, and flooding events. Whether and how people respond to increased hazard exposure (adaptive behavior) is widely recognized to be driven by their capacity to adapt, perception of the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 64 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…In contrast to other socio-hydrological models, human behavior is included in more detail and based on behavioral or psychological models, of which the Protection-Motivation-Theory (PMT; Rogers, 1983) has become the most popular one since Grothmann and Reusswig (2006) applied it successfully to explain flood adaptive behavior in the city of Cologne, Germany. Coping appraisal was found to be particularly important; it consists of perceived self-efficacy, perceived response efficacy, and perceived costs of adaptation (response costs) and is enhanced by observational learning from the social environment, such as friends and neighbors (Bubeck et al, 2018) highlighting the role of social capital and norms (Bixler et al, 2021). In fact, a review (van Valkengoed & Steg, 2019) across different hazards, designs, and countries revealed that self-efficacy, response efficacy, negative affect, and descriptive norms are the best predictors for adaptive behavior, while risk perception and experience show just small to moderate effects although they are more frequently studied.…”
Section: Capacity and Adaptationmentioning
confidence: 99%
“…In contrast to other socio-hydrological models, human behavior is included in more detail and based on behavioral or psychological models, of which the Protection-Motivation-Theory (PMT; Rogers, 1983) has become the most popular one since Grothmann and Reusswig (2006) applied it successfully to explain flood adaptive behavior in the city of Cologne, Germany. Coping appraisal was found to be particularly important; it consists of perceived self-efficacy, perceived response efficacy, and perceived costs of adaptation (response costs) and is enhanced by observational learning from the social environment, such as friends and neighbors (Bubeck et al, 2018) highlighting the role of social capital and norms (Bixler et al, 2021). In fact, a review (van Valkengoed & Steg, 2019) across different hazards, designs, and countries revealed that self-efficacy, response efficacy, negative affect, and descriptive norms are the best predictors for adaptive behavior, while risk perception and experience show just small to moderate effects although they are more frequently studied.…”
Section: Capacity and Adaptationmentioning
confidence: 99%
“…Our research is situated in a literature base that is diversified, growing and evolving, and spread across many disciplines focused on urban and community resilience (Aldrich and Meyer, 2015;Brunetta et al, 2019;Caldarice et al, 2019;Scherzer et al, 2019), adaptive capacity in relation to hazard preparedness (Pfefferbaum et al, 2013;Onuma et al, 2017;Siders, 2019;Bixler et al, 2021a), and vulnerability (Cutter et al, 2003;Adger, 2006;McDowell et al, 2016;Flanagan et al, 2018). The intersection of climate-related hazards, social vulnerability, and urban communities has become a central component of an international climate change adaptation research and policy agenda (Siders, 2019;Nalau and Verrall, 2021;Shi and Moser, 2021).…”
Section: Climate Impacts and Community Resiliencementioning
confidence: 99%
“…In addition to exposure and sensitivity, adaptive capacity is another dimension of vulnerability and urban resilience frequently considered in the literature (Pfefferbaum et al, 2013;Elrick-Barr et al, 2014;Bixler et al, 2021a;Shi and Moser, 2021;Bixler and Jones, 2022). Climate impacts are most acutely experienced at the household scale and thus increasing adaptive capacity of households is both a short-term necessity in hazard prone neighborhoods and a critical long-term hazard risk reduction strategy.…”
Section: Climate Impacts and Community Resiliencementioning
confidence: 99%
“…Among essential community characteristics, community social capital, which reflects the set of collective values, norms, and beliefs, can be transferred to resources and bring tangible benefits to community members ( Borgonovi, Andrieu, and Subramanian 2021 ; Glanville, Paxton, and Wang 2016 ). Social capital leads to civic engagement embedded in social interaction, ties, and structures, which motivates people to mobilize resources through protective or adaptive action in response to external disturbances ( Bixler et al 2021 ; Lin, Fu, and Hsung 2001 ). The collective ability for resource mobilization, in turn, determines the success of the post-disaster recovery ( Aldrich 2012 ).…”
Section: Introductionmentioning
confidence: 99%